Blue Band Advertisements in Newspapers From 1900 - Tampubolon, Jimmy Saputra; Pangaribuan, Juli; Deswita, Nadya (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2024)
This article explores the journey of a Jewish family business, starting from margarine sales in the Netherlands to the development of the iconic Blue Band brand in Indonesia. Beginning with Tomor margarine, specifically targeted at the Jewish community, the Van de Berg family eventually merged with other companies to form Unilever in 1930. Since its introduction in 1934, Blue Band has become an integral part of Indonesian society, accompanying the country's social, economic, and political development. This qualitative research aims to delve into the long history of Blue Band in Indonesia, analyze its innovative strategies in maintaining its market position, and understand its impact on consumption patterns and public perception of margarine. Through an in-depth literature review, this research is expected to provide comprehensive insights into how Blue Band has become one of the most trusted and beloved food brands in Indonesia.